The extended generalized Riccati equation mapping method for the (1+1)-dimensional modified KdV equation - Naher, Hasibun; Abdullah, Farah Aini; Akbar, M. Ali; Yildirim, Ahmet (© 2013 IDOSI Publications, 2016)
This article was published in the World Applied Sciences Journal [©2013 IDOSI Publications] and the definite version is available at: 10.5829/idosi.wasj.2013.25.04.2980